027 Promoting atraumatic needle usage for lumbar puncture in neurology: the power of the default. Issue 12 (14th November 2019) - Holland, Christian; Moore, Catherine; Tobert, Vanessa; Allen, James; Moore, Thomas; Durley, Kirsty; Edmond, Evan
Abstract : Lumbar puncture (LP) is a key diagnostic investigation in neurology. Post-dural puncture headache (PDPH) is a known complication of lumbar puncture, resulting in significant patient morbidity. Fine-gauge and atraumatic-tip needles have been shown to reduce significantly the risk of PDPH. While uptake of such needles has been universal in anaesthetics, neurology has lagged behind. Here we investigate a multimodal intervention to increase the usage of atraumatic needles in neurology. Over a 15 month period, LPs were reviewed at the neurology day case unit of the John Radcliffe Hospital, a large tertiary centre. We present results from 218 LPs performed, and outcome data including documentation score and atraumatic needle usage. Simulation training interventions were associated with moderate improvement in practice, with a gradual reduction over time. This may be associated with staff turnover. Changing the default needle to an atraumatic (Sprotte 22G) needle was associated with a marked and sustained improvement in practice. There was no difference in success rate with the new needle and proforma usage remained high. Default options have previously been shown to be a powerful determinant of human behaviour in clinical medicine. Our results suggest that this may be an important tool to improve clinical practice in LP in Neurology, though staff engagement and monitoring for unintended consequences of changes in default equipment are essential.